A Photoinduced Palladium-Catalyzed Cascade Reaction for the Synthesis of Chiral Piperidines with Chiral Amino Acid Derivatives and 1,3-Dienes - Song, Shun; Yin, Yi-Zhuo; Han, Zhi-Yong (Synthesis, 2023)
A photoinduced palladium-catalyzed cascade reaction involving remote C(sp3)–H functionalization and intramolecular Tsuji–Trost annulation is developed. The reaction is proposed to proceed through a sequence involving the amidyl radical generation, 1,5-HAT-mediated alkyl radical formation, and subsequent difunctionalization of 1,3-dienes. Without the use of exogeneous photosensitizers and external oxidants, the reaction provided an efficient approach to multi-substituted chiral piperidines in high yields, employing readily available chiral amino acid derivatives and 1,3-dienes as the substrates. In most cases, the syn/anti ratio of the product could be further improved by treatment with catalytic amount of iron salt.
Keywords: excited-state Pd catalysis; chiral piperidines; amino acids; 1,3-dienes; Tsuji–Trost annulation